Sexuality and Gender in Educational Documents in the State of São Paulo - Fábio Martins Gaioli; Ana Paula Leivar Brancaleoni; Caio Samuel Franciscati da Silva; Rosemary Rodrigues Oliveira (Universidade Cruzeiro do Sul, Ensino de Ciências e Matemática, 2022)
Research on sexuality and access to education that there are, for example, school subjects and permanence of LGBTQIAP+ school studies. This study aims to verify possible conceptions of sexual and gender diversity in documents oriented to basic education in the State of São Paulo (Diálogos e práticas restaurativas na escola: Guia prático para educadores e Resolução SE 8, de 31 de janeiro de 2018) and their possible to the teaching action related to thematic contributions. The results point to silencing of sexual and gender diversity and, in a broad context, indeterminacy of the concepts of diversity, difference and tolerance.